Epidemiological Peculiarities of Ebola Virus Disease Epidemic, 2013-2015 in West Africa Countries - A. Yu. Popova; V. A. Safronov; M. Y. Boiro; E. V. Kouklev; O. V. Kedrova; S. K. Udovichenko; A. A. Lopatin; A. S. Razdorsky; E. B. Ezhlova; V. Yu. Smolensky; V. V. Kutyrev (Проблемы особо опасных инфекций, 2015)
Represented are the results of analysis of the on-going EVD epidemic, 2013-2015 in West Africa countries. Identified have been epidemiological peculiarities, the principal ones of which are: the scale of epidemic transmission; social factors of widespread occurrence; registration of EVD cases in the new territories of the African continent - West Africa (Guinea, Liberia, Sierra-Leone); genetic distinction between Ebola virus and the strains of the same virus, species Zaire ebolavirus, that caused previous outbreaks; prevalence of febrile syndrome over hemorrhagic; high risk of infection with EVD among the healthcare workers. Most probable carriers of Ebola virus may be fruit-bats of the three species - Hypsignathus monstrosus, Myonycteris torquata, and Epomops franqueti. Outlined are the key stages and factors of EVD epidemic development.